2011
DOI: 10.4315/0362-028x.jfp-11-284
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NaCI and NaNO3 on Sinigrin Hydrolysis by Foodborne Bacteria

Abstract: The glucosinolate sinigrin (SNG) is converted by endogenous plant myrosinase or by bacterial myrosinase-like activity to form the potent antimicrobial allyl isothiocyanate. In order to use SNG as a natural antimicrobial precursor in food, it became important to better understand the ability of bacteria to synthesize the enzyme(s) and understand factors influencing this synthesis at a constant SNG concentration. Eight spoilage, pathogenic, or starter culture bacteria were grown separately in medium containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Since AITC is difficult to measure accurately in aqueous media because it is volatile and easily decomposes to new products under these circumstances (Liu and Yang, 2010), sinigrin degradation was used as a more dependable measure of its formation. Further, it was evident that C. jejuni strains possess myrosinase-like enzyme(s) as has been observed with many other foodborne bacteria (Herzallah et al, 2011) and were able to degrade 87% to 91% (975 to 1020 ppm) of the sinigrin present in buffered MH broth (pH 7.0) by 21 d at 35°C (Table 3). Although sinigrin hydrolysis by C. jejuni at 35°C was greater than that at 4°C, the AITC formed is more stable at 4°C (Olaimat and Holley, 2013).…”
Section: Viability Of C Jejuni On Chicken Breastsmentioning
confidence: 87%
“…Since AITC is difficult to measure accurately in aqueous media because it is volatile and easily decomposes to new products under these circumstances (Liu and Yang, 2010), sinigrin degradation was used as a more dependable measure of its formation. Further, it was evident that C. jejuni strains possess myrosinase-like enzyme(s) as has been observed with many other foodborne bacteria (Herzallah et al, 2011) and were able to degrade 87% to 91% (975 to 1020 ppm) of the sinigrin present in buffered MH broth (pH 7.0) by 21 d at 35°C (Table 3). Although sinigrin hydrolysis by C. jejuni at 35°C was greater than that at 4°C, the AITC formed is more stable at 4°C (Olaimat and Holley, 2013).…”
Section: Viability Of C Jejuni On Chicken Breastsmentioning
confidence: 87%
“….06-10 (6 d) NT [28] Pediococcus acidilactici + 7 NT NT 2.92-3.16 (6 d) NT [28] Pediococcus pentosaceus + 1 9 NT 11.99 (12 d) NT [29] Escherichia coli 0157:H7 − 1 9 NT 38.96 (12 d) NT [29] Listeria monocytogenes + 1 9 NT 19.04 (8 d) NT [29] Escherichia fecalis + 1 9 NT 9.05 (12 d) NT [29] Staphylococcus aureus + 1 9 NT 20.39 (8 d) NT [29] Staphylococcus carnosus + 1 9 NT 21.2 (8 d) NT [29] Salmonella typhimurium − 1 9 NT 28.02 (12 d) NT [29] Pseudomonas fluorescens − 1 9 NT 7.17 (12 d) NT [29] Listeria monocytogenes + 1 9 NT 53.2 (21 d, 21°C) NT [92] Salmonella − 1 9 NT 59.9 (21 d, 21°C) NT [92] The presence or absence of the typical products, that is, ITC and/or nitrile, are indicated. % GSL conversion is given as the least to the maximum value for any number of isolates while E. casseliflavus CP1 was able to metabolize all GSLs tested to nitriles and ITCs with the exception of glucoraphanin and glucoiberin where only trace amounts of ITCs and nitriles were observed.…”
Section: Isothiocyanate Productionmentioning
confidence: 99%
“…Further studies involved screening a variety of bacteria including E. coli 0157:H7 with sinigrin as a substrate with all strains producing allylisothiocyanate. [29] More recent work with the GSL metabolizing E. coli 0157:H7 identified genes bglA and ascbB encoding 6-phospho-β-glucosidases. [30] Following gene disruption, the sinigrin degrading ability of this organism was substantially reduced.…”
Section: Isothiocyanate Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that glucosinolates also can be degraded by different bacterial species that possess myrosinase-like activity, such as Lactobacillus agilis (26), Bacillus and Staphylococcus (4), Bacteroides thetaiotaomicron (7), human fecal microflora (16), Bifidobacterium pseudocatenulatum, Bifidobacterium adolescentis, Bifidobac terium longum (5), Pediococcus pentosaceus, Staphylococ cus carnosus, Escherichia coli 0157:H7 (10), Lactobacillus curvatus and Lactobacillus plantarum (20), Salmonella Typhimurium, Enterococcus faecalis, and L. monocyto genes (11). It currently is unknown whether bacteria have more than one enzyme capable of hydrolyzing glucosinolates.…”
mentioning
confidence: 99%